1988
DOI: 10.1182/blood.v71.3.753.bloodjournal713753
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and expression of binding sites specific for ferritin H- chain on human cell lines

Abstract: Purified recombinant human ferritin composed solely of H subunit was radiolabeled and incubated with proerythroleukemic K562 human cells. A specific binding was detected, and it could be displaced only by ferritins, natural or recombinant, containing large proportion of the H subunit. The specific ferritin H-chain binding was saturable, and cells showed 17,000 to 23,000 binding sites per cell. The affinity constant measured at 37 degrees C was of 3 x 10(8) M-1. Treatment with pronase eliminated the specific bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Despite extensive biochemical, cytological, and genetic study of vertebrate and insect ferritins, their functions (in particular that of the secreted form of ferritin) at systemic, cellular, and molecular levels are not completely elucidated. A great deal of research effort has shown that mammalian serum ferritin can bind to a variety of cell types in a specific, saturable manner and undergo endocytosis with subsequent iron delivery (8,12,13). Several ferritin receptors on the surface of certain cell types or ferritin interaction proteins in plasma were even identified recently (12,14,15).…”
mentioning
confidence: 99%
“…Despite extensive biochemical, cytological, and genetic study of vertebrate and insect ferritins, their functions (in particular that of the secreted form of ferritin) at systemic, cellular, and molecular levels are not completely elucidated. A great deal of research effort has shown that mammalian serum ferritin can bind to a variety of cell types in a specific, saturable manner and undergo endocytosis with subsequent iron delivery (8,12,13). Several ferritin receptors on the surface of certain cell types or ferritin interaction proteins in plasma were even identified recently (12,14,15).…”
mentioning
confidence: 99%
“…An immunosuppressive role for ferritin has also been proposed, based on !ts ability to inhibit mitogen-stimulated lymphocyte proliferation ( 121,122). The recent characterisation of ferritin receptors on a number of different cell types ( 123,124) supports the idea that ferritin may regulate certain cell functions.…”
Section: Function Of Ferritinmentioning
confidence: 86%
“…for H-ferritin. Their expression was induced by cellular proliferation and iron depletion and in K562 cells it was suppressed by hemin induced differentiation [22]. A relation between the expression of H-ferritin binding sites and H-ferritin suppressive activity was suggested.…”
Section: Introductionmentioning
confidence: 92%
“…Ferritin binding was performed as described by Fargion et al [22]. Briefly, 2 X lo5 fetal liver erythroblasts and erythroblasts collected on the various days of BFU-E cultures, erythrocytes, and reticulocytes were incubated at 37°C for 60 min with saturating concentrations of radioiodinated rHF and rLF, in 50 ~1 of phosphate-buffered saline containing 1 mg/mL of bovine serum albumin.…”
Section: Ferritin Bindingmentioning
confidence: 99%
See 1 more Smart Citation